Food Consumption and Iron Status Survey in Two Provinces of Rural Burkina Faso - Institut de Recherche pour le Développement; Institut de Recherche en Sciences de la Santé; International Food Policy Research Institute (International Food Policy Research Institute, 2016)
In Burkina Faso very little is known about levels of vitamin A, iron, and zinc deficiencies. The lack of detailed knowledge about food and nutrients intake and deficiency levels is a substantial obstacle to the design, implementation and evaluation of effective food-based interventions such as biofortification. The present study, a preliminary study of a sorghum biofortification project, was conducted to contribute to fill that knowledge gap in two rural provinces of Burkina Faso. Its objectives were: (i) to provide reliable information on sorghum consumption, micronutrient intakes and micronutrient deficiencies among women of reproductive age and their preschool children, in order to better inform sorghum micronutrient content breeding targets and future interventions; and (ii) to investigate the relationship between biomarkers of status and dietary intakes of iron, zinc and vitamin A among the study subjects in order to better inform the evaluation design of future biofortification interventions. This work is part of the Grand Challenges in Global Health (#9), an initiative of the Bill and Melinda Gates Foundation through a grant to the International Food Policy Research Institute; with additional funds from the Institut de Recherche pour le Développement.